2018
DOI: 10.1680/jwama.16.00051
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of anti-vortex devices at water intakes

Abstract: The formation of vortices above the submerged discharge intakes of water reservoirs is undesirable as they can suck surface debris and air into the discharge pipework. In the present work, a numerical investigation was performed on the performance of an anti-vortex device at the water intake. The numerical simulation of the flow field around a free-surface vortex was verified with experimental data, with good agreement found on radial velocity and vortex type. The lateral shape of the anti-vortex device was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Their numerical simulations were validated with experimental data. Their analysis on the type of vortex and radial velocity was in good agreement with the experimental results [23]. Khadem Rabe et al (2017) numerically simulated the air-core vortex at an intake.…”
supporting
confidence: 66%
“…Their numerical simulations were validated with experimental data. Their analysis on the type of vortex and radial velocity was in good agreement with the experimental results [23]. Khadem Rabe et al (2017) numerically simulated the air-core vortex at an intake.…”
supporting
confidence: 66%
“…The numerical model data is the output of the STAR-CCM + . Khadem Rabe et al [17,18] used the STAR-CCM + in a study of the simulation of the vortex core and compared their results with different experimental and numerical studies. Therefore, it could be deduced that STAR-CCM + software has reasonable accuracy in simulating free-surface vortices.…”
Section: Verification Of the Numerical Modelmentioning
confidence: 99%
“…They concluded that cavitation would increase the boundary layer of the stream and exacerbate the vortex air-core. Khadem Rabe et al [17,18] conducted numerical simulations to examine the behavior of the flow when the vortex air-core was pulled into the basin. In this research, tangential, radial, and axial velocity components, and water surface profiles were evaluated for an in-depth understanding of the flow patterns and to work out the depth of critical submersion.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous model tests conducted at a reduced scale, those presented by Kucukali and Hassinger (2018) were performed at a scale of 1:1 to avoid viscosity scale effects. In the tested fish pass with a bed slope of 4%, multiple continuous migration corridors were found, without obstructions for the fish to overcome or flow regime changes.Complementary to laboratory experiments, advanced 3D numerical modelling was used by Khadem Rabe et al (2018) to simulate the flow near an anti-vortex system at a water intake. Although avoiding vortices at water intakes is of utmost importance (as they can suck surface debris and air into the pressurised flow system), considerable gaps in knowledge remain regarding the prediction and characterisation of vortex generation.…”
mentioning
confidence: 99%
“…Complementary to laboratory experiments, advanced 3D numerical modelling was used by Khadem Rabe et al (2018) to simulate the flow near an anti-vortex system at a water intake. Although avoiding vortices at water intakes is of utmost importance (as they can suck surface debris and air into the pressurised flow system), considerable gaps in knowledge remain regarding the prediction and characterisation of vortex generation.…”
mentioning
confidence: 99%